The awareness of hydration knowledge on gender differences among UiTM Perlis athletes / Fatin Najihah Abd Rashid - Abd Rashid, Fatin Najihah (2021)
Water is the human body's main constituent. Paucity of hydration can impair the sports performance of the athletes and cause heat problems which can harm the athletes. Therefore, maintaining proper hydration status is crucial for sports performance and general well-being of athletes. Previous study focused on hydration knowledge among difference participants and focused on one type of gender only. To date, no clear results on hydration knowledge between genders among university athletes. Therefore, the purpose of this study was to determine the hydration knowledge on gender differences among UiTM Perlis athletes. A total of 169 UiTM Perlis athletes (85 males and 84 females) were participated in this study. Athletes were asked to answer Hydration Awareness Questionnaire (HAQ) which consists of 13 items. This study utilized online survey questionnaires to assess athlete hydration knowledge. The results of this study indicate that there was no substantial difference (p > 0.05) observed between genders in hydration knowledge. Despite understanding the importance of keeping hydrated, the awareness between genders on the hydration knowledge was on the average. Therefore, continued efforts must be made by coaches, managers and athletes to develop and implement more effective hydration strategies.